Model of NBTI combined with mobility degradation *Project supported by the Shenzhen Science and Technology Project (Nos. ZDSYS201703031405137, JCYJ20170810163407761, (JCYJ20170818114156474), the PhD Start-up Fund of Natural Science Foundation of Guangdong Province (No. 2015A030310499), and the China Postdoctoral Science Foundation Funded Project (No. 2015T80023). (December 2018) - Wu, Xuezhong; Ma, Chenyue; Gao, Shucheng; Li, Xiangbin; Sun, Fu; Zhang, Lining; Lin, Xinnan
Abstract: The mobility degradation induced by negative bias temperature instability (NBTI) is usually ignored in traditional NBTI modeling and simulation, resulting in overestimation of the circuit lifetime, especially after long-term operation. In this paper, the mobility degradation is modeled in combination with the universal NBTI model. The coulomb scattering induced by interface states is revealed to be the dominant component responsible for mobility degradation. The proposed mobility degradation model fits the measured data well and provides an accurate solution for evaluating coupling of NBTI with HCI (hot carrier injection) and SHE (self-heating effect), which indicates that mobility degradation should be considered in long-term circuit aging simulation.